Circularly permuted tRNA genes: their expression and implications for their physiological relevance and development - Soma, Akiko (Frontiers in Genetics, 2014)
A number of genome analyses and searches using programs that focus on the RNA-specific bulge-helix-bulge (BHB) motif have uncovered a wide variety of disrupted tRNA genes. The results of these analyses have shown that genetic information encoding functional RNAs is described in the genome cryptically and is retrieved using various strategies. One such strategy is represented by circularly permuted tRNA genes, in which the sequences encoding the 5′-half and 3′-half of the specific tRNA are separated and inverted on the genome. Biochemical analyses have defined a processing pathway in which the termini of tRNA precursors (pre-tRNAs) are ligated to form a characteristic circular RNA intermediate, which is then cleaved at the acceptor-stem to generate the typical cloverleaf structure with functional termini. The sequences adjacent to the processing site located between the 3′-half and the 5′-half of pre-tRNAs potentially form a BHB motif, which is the dominant recognition site for the tRNA-intron splicing endonuclease, suggesting that circularization of pre-tRNAs depends on the splicing machinery. Some permuted tRNAs contain a BHB-mediated intron in their 5′- or 3′-half, meaning that removal of an intron, as well as swapping of the 5′- and 3′-halves, are required during maturation of their pre-tRNAs. To date, 34 permuted tRNA genes have been identified from six species of unicellular algae and one archaeon. Although their physiological significance and mechanism of development remain unclear, the splicing system of BHB motifs seems to have played a key role in the formation of permuted tRNA genes. In this review, current knowledge of circularly permuted tRNA genes is presented and some unanswered questions regarding these species are discussed.